Ultrastructural and molecular approach as a tool for taxonomic identification of aquatic macroinvertebrates: A review. Issue 12 (December 2022) - Grover, Aseem; Sharma, Parul; Sharma, Radhika; Sinha, Reshma
Abstract: Aquatic insects require water at one or other phase for the completion of their life cycle. The insect larvae serve as food for larger invertebrates and vertebrates in aquatic food chain. Their diversity, number, and abundance act as water quality indicators, and thus species are classified accordingly as pollution tolerant or sensitive. So, identifying these aquatic larvae and macroinvertebrates are important for determining the biodiversity, and classification of insect species, followed by assessment of water health, and understanding the influence of climate change and anthropogenetic activities on these. Chances of misidentification have been reported due to loss of expertise, absence of taxonomic keys for larvae or intermediate stages, or damaged structure during collection or preservation. Recent advances in molecular and electron microscopy have revolutionized the identification procedure. Scanning electron microscopy detail the structure and morphology of the insect, while molecular techniques employing PCRs, DNA barcoding, and molecular markers allow the identification of the insects from any tissue (whole/part), and comparing the nucleotide sequences helps in the evaluating the family tree and lineage. The review summarizes the present status of aquatic invertebrates identification and the importance of these two techniques in the taxonomic identification of aquatic insects. Abstract : Aquatic insects; Macroinvertebrates; Molecular markers; Electron microscopy; DNA barcoding.